Isolation and number of circulated primordial germ cells (circulated-PGCs) on stages of embryonic development of Gaok chicken - T, Kostaman; TL, Yusuf; M, Fahrudin; MA, Setiadi (Indonesian Animal Sciences Society, 2013)
Avian primordial germ cell (PGCs) show a unique migration pathway during early development. During the early embryonic development, as soon as the formation of blood vessels, PGCs enter the circulatory system and migrate to the gonadal primordial. The aim of this study was to examine the number of circulated-PGCs from Gaok chicken at different developmental stages of embryo. One hundred fertile eggs were divided into 5 groups and incubated in a portable incubator at 38oC and humidity 60%. Hatching was set according to the embryonic development stage between 14-18. The blood collection was done through the dorsal aorta using micropipette under microscope. The collected blood was grouped based on the embryonic stages and placed on a 1.5 ml eppendorf tube which had been filled with 1.000 µl of Calcium and Magnesium-free phosphate buffered saline (PBS -). The PGCs were then purified using nycodenz density gradient centrifugation. The results showed that the average number of circulated-PGCs per embryo from Gaok chicken were significantly affected by the stage of embryonic development (P < 0.05). The number of circulated-PGCs at stages 14, 15, 16, 17 and 18 were 42.8 ± 8.9, 51.0 ± 5.8, 37.6 ± 5.9, 32.8 ± 3.6 and 32.6 ± 3.2, respectively. However, the number of circulated-PGCs was no different between stage of 17 and 18. At Gaok chicken, the number of circulated-PGCs reach the peak at stage 15, it is recommended that collection of PGCs embryonic chicken from blood circulation was the best on stage 15. This information is useful in efficiency production of germline chimera and to preserve PGCs of other Indonesian native chicken. Key Words: Gaok Chicken, PGCs, Embryonic Development Stages